2019
DOI: 10.1002/cssc.201802974
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reverse Semi‐Combustion Driven by Ionic Liquids

Abstract: Supporting Information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The photoreduction of CO 2 was first performed in aqueous solution of ILs, [21] without the presence of TiO 2 ( There is a noteworthy influence of the anion on CO 2 photoreduction (Table 1, entries 1-5). CO is produced only with ILs containing basic anions (imidazolate), indicating their involvement (direct or indirect) on the CO 2 activation, H 2 O oxidation, and probably also on the confinement of the photocatalyst active sites in water-deficient media, in which the CO 2 reduction mechanism follows distinct reaction pathways than in H 2 O-rich media (i. e., higher H 2 selectivity in H 2 O-rich media).…”
Section: Resultsmentioning
confidence: 99%
“…The photoreduction of CO 2 was first performed in aqueous solution of ILs, [21] without the presence of TiO 2 ( There is a noteworthy influence of the anion on CO 2 photoreduction (Table 1, entries 1-5). CO is produced only with ILs containing basic anions (imidazolate), indicating their involvement (direct or indirect) on the CO 2 activation, H 2 O oxidation, and probably also on the confinement of the photocatalyst active sites in water-deficient media, in which the CO 2 reduction mechanism follows distinct reaction pathways than in H 2 O-rich media (i. e., higher H 2 selectivity in H 2 O-rich media).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in various cases, the interaction of the IL pair changes the reactivity of the trapped water, which can easily react with substrates, products, and even with the IL. [8,9,19,[27][28][29][30] In this contribution, the different modes of interaction of CO 2 with bare ILs containing both nonbasic and mainly basic anions will be presented and discussed critically, considering recent examples reported in the literature. Finally, it will be demonstrated that simple concepts of acid-base chemistry can be used to explain and to design new ionic fluids for CO capture and activation.…”
Section: Introductionmentioning
confidence: 99%
“…The initiator, AIBN, was 1% of the mass of the monomers. The mixture was vortexed, sonicated, and degassed until homogeneous, then poured Standard procedure for the preparation of polymers [15][16][17][18][19][20] The corresponding SILLP (500 mg, 5-7 and 11-13)w as suspended in as olution of RB (20 mL, 1000 ppm in MeOH) and left under stirring for 24 h. Then, the polymer was filtered, washed with MeOH (3 20 mL), and dried in av acuum oven at 45 8C. The absorption for RB at 557 nm was measured in the mother liquor and in the washing liquid.…”
Section: Synthesis Of 1-[(4-ethenylphenyl)methyl]-3-butyl-imidazoliummentioning
confidence: 99%
“…Ionic liquids( ILs) have been evaluated as alternative reaction media for awide range of catalytic processes [12][13][14] and also represent as imple and tunable alternative fort he immobilization and stabilization of photosensitizers, opening new avenues for photocatalytic synthetic processes. [15][16][17][18][19][20][21][22][23] However,p rocesses involvingh omogeneous ILs require the full recovery of the ILphase and the photosensitizer in af urther step, which is not always as imple task. The simplest solution is represented by the use of supported ILs (SILs).…”
Section: Introductionmentioning
confidence: 99%